GnRH-1 Neural Migration From the Nose to the Brain Is Independent From Slit2, Robo3 and NELL2 Signaling - Taroc, Ed Zandro M.; Lin, Jennifer M.; Tulloch, Alastair J.; Jaworski, Alexander; Forni, Paolo E. (Frontiers in Cellular Neuroscience, 2019)
GnRH-1 neurons play a pivotal role in controlling pubertal onset and fertility once they reach their hypothalamic location. During embryonic development, GnRH-1 neurons migrate from the nasal area to the hypothalamus where they modulate gonadotropin release from the pituitary gland. Defective migration of the GnRH-1 neurons to the brain, lack of GnRH-1 secretion or signaling cause hypogonadotropic hypogonadism (HH), a pathology characterized by delayed or absence of puberty. Binding of the guidance cue Slit2 to the receptor Robo3 has been proposed to modulate GnRH-1 cell motility and basal forebrain access during migration. However, evidence suggests that NELL2, not Slit2, binds to Robo3. To resolve this discrepancy, we analyzed GnRH-1 neuronal migration in NELL2, Robo3, and Slit2 knock-out mouse lines. Our data do not confirm a role for Robo3 and Slit2 in controlling GnRH-1 neuronal migration from the nasal area to the brain. Moreover, we found no changes in GnRH‑1 neuronal migration in the brain after NELL2 loss-of-function. However, we found that Slit2 loss-of-function alters the patterning of GnRH-1 cells in the brain, suggesting that Slit2 loss of function affects GnRH-1 cell positioning in the brain in a Robo3 independent fashion. Our results challenge previous theories on GnRH-1 neuronal migration mechanisms and provide a new impetus to identify genetic mechanisms causing disorders like Kallmann Syndrome and hypogonadotropic hypogonadism.